Placental vasculogenesis and angiogenesis in women undergoing chemotherapy - Yu.E. Dobrokhotova; E.I. Borovkova; A.M. Arutyunyan; S.Zh. Danelyan; E.M. Malysheva; N.V. Zharkov; T.N. Aksenova (LCC «Medicine-Inform», 2021)
Yu.E. Dobrokhotova1, E.I. Borovkova1, A.M. Arutyunyan1, S.Zh. Danelyan2, E.M. Malysheva2, N.V. Zharkov2,3, T.N. Aksenova2 1 Pirogov Russian National Research Medical University, Moscow, Russian Federation 2City Clinical Hospital No. 40, Moscow, Russian Federation 3 I.M. Sechenov First Moscow State Medical University (Sechenov University), Moscow, Russian Federation Aim: to study placental vasculogenesis and angiogenesis in women receiving chemotherapy. Patients and Methods: placental structure was examined in 57 pregnant women aged 22-38 years who were subdivided into 3 groups, i.e., women with malignancies receiving or not receiving chemotherapy and healthy controls. The slices of the central part of placentas collected after childbirth were examined. Immunohistochemistry (IHC) was performed after standard histology. IHC intensity was assessed for CD31 and CD34. In addition to IHC intensity, the number of positive cells per field of view was calculated for VEGF, VEGFR1, and VEGFR2. Mean counts of positive cells separately for epithelial and stromal cells were calculated for eNOS. Results: in the control group, the maturity of the placental villous tree matched the gestational age. Meanwhile, in 100% of pregnant women with malignancies receiving chemotherapy and in 46.8% of pregnant women with malignancies not receiving chemot herapy, the maturity of the placental villous tree was 2-4 weeks behind the gestational age. IHC revealed no significant differences in the placental concentrations of CD31, CD39, eNOS, VEGF, VEGFR1, and VEGFR2 between women with malignancies not receiving chemotherapy and the controls. In women receiving chemotherapy, IHC intensity and the number of positive cells were twice as high as in the control group. The activity of VEGFR1 and VEGFR2 was 11 times higher and 1.4 times higher, respectively, than in the control group. The mean number of cells expressing VEGFR1 and VEGFR2 per field of view increased by 1.5 times and 1.7 times, respectively. In addition, 1.6-fold reduction in CD31 level and 1.3-fold reduction in CD34 level as well as 1.4-fold increase in epithelial еNOS level and 1.3-fold increase in stromal eNOS level were revealed. Conclusions: our findings on IHC distribution of the expression of VEGF and its recep-tors in the placental tissue of pregnant women undergoing cytostatic chemotherapy in part illus-trate the processes of the compensation and impaired functioning of the mother-placenta-fetus system in pre-placental hypoxia. Keywords: angiogenesis, vasculogenesis, vascular growth factor, chemotherapy, hypoxia, placental insufficiency. For citation: Yu.E. Dobrokhotova, Borovkova E.I., Arutyunyan A.M., Danelyan S.Zh. et al. Placental vasculogenesis and angiogenesis in women undergoing chemotherapy. Russian Journal of Woman and Child Health. 2021;4(1):23-30. DOI: 10.32364/2618-8430-2021-4-1-23-30.